Hubungan Status Gizi terhadap Kualitas Hidup Pasien Kanker Payudara Stadium 1 dan 2 di RS Tugurejo Semarang - Nirrana Wulan Rizki; Risky Ika Riani; Afiana Rohmani (Jurnal Ilmiah Kedokteran dan Kesehatan, 2026)
Poor nutritional status in breast cancer patients may increase living expenses, fatigue, and limitations in daily activities, resulting in decreased quality of life. Patients with stage 1 and 2 breast cancer generally have better quality of life due to optimal treatment and better physical and psychological conditions. This study aimed to examine the relationship between nutritional status and quality of life among stage 1 and 2 breast cancer patients at Tugurejo Hospital Semarang. This analytical observational study used a cross-sectional approach involving 42 breast cancer patients. Nutritional status was assessed using Body Mass Index (BMI), while quality of life was measured using the WHOQOL-BREF questionnaire. Data were analyzed using the Spearman rank test. The results showed that 4 respondents (9.5%) were underweight, 23 respondents (54.8%) had normal BMI, and 15 respondents (35.7%) were obese. Regarding quality of life, 4 respondents (9.5%) had moderate quality of life and 38 respondents (90.5%) had high quality of life. The Spearman rank test showed a p-value of 0.034 (<0.05) with a correlation coefficient of 0.328, indicating a sufficient relationship between nutritional status and quality of life. In conclusion, nutritional status is related to the quality of life of stage 1 and 2 breast cancer patients at Tugurejo Hospital Semarang.